Data-driven hybrid approaches for renewable power prediction toward grid decarbonization: Applications, issues and suggestions - Hossain Lipu M.S.; Miah M.S.; Ansari S.; Hannan M.A.; Hasan K.; Sarker M.R.; Mahmud M.S.; Hussain A.; Mansor M. (Elsevier Ltd, 2023)
Decarbonization; Electric power transmission networks; Forecasting; Fossil fuels; Global warming; Solar energy; Data driven; Data-driven algorithm; Data-driven approach; Data-driven methods; Decarbonisation; Hybrid approach; Hybrid datum; Optimisations; Power predictions; Renewable Power; Wind power